The islamic republic of Iran’s hegemony in Iraq, the cause, effect, and consequences - Wzhar Fahri Saadi (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
Iran’s influence on the Iraqi government is very significant since the fall of the baath regime in 2003, with Iran trying to impose its aims and bring a voluntary government to power throughout the new Iraqi government. In contrast, the United States and its Arab allies oppose Iran’s interference in Iraq’s internal affairs. Their concerns are that Iran’s influence has extended to support armed groups in Iraq, US officials say, Shia militants in Iraq receive weapons and the necessities from Iran to attack US forces in Iraq. This Iranian policy against the United States is welcomed by the enemies of the United States, such Russia and China. On the other hand, the rise of the ISIS terrorist group gave Iran a golden opportunity to impose it’s hegemony through the creation of the Popular Mobilization Forces (Hashd al Shaabi). Iran paid the price for its interference in Iraq. they lost their commander (Qassem Soleimani) who has been killed by the US forces in Baghdadز